Penggunaan Media Permainan Congklak sebagai Konteks Masalah Realistik Pada Pembelajaran KPK dan FPB Kelas 5 - Fauziyani, Witrinia; Wardani, Karina; Zuliana, Eka (Program Studi Pendidikan Matematika FKIP UNIVA Medan, 2025)
Mathematics education in elementary school often encounters obstacles, especially in abstract concepts such as LCM and GCD. Many students have difficulty understanding this material, which is often considered boring and difficult. One of the efforts that can optimize students' knowledge is by using interactive interactive learning media, such as the traditional game of congklak. This study focuses on analyzing the use of congklak game media as a realistic problem context in learning KPK and FPB in grade 5 of SDN Jambean 03. This study uses a descriptive qualitative method, with data collection through observation, interviews, and documentation. This study aims to connect mathematical concepts with daily experiences or relevant activities in students' lives, with the use of the KPK and FPB congklak game utilized as a useful tool to provide a real context or context of realistic problems in the learning process The results showed that the use of congklak media as a learning tool that can make students understand the learning of KPK and FPB.